Religious discourse in modern Japan : religion, state, and Shinto - Isomae, Jun'ichi, 1961- (Dynamics in the History of Religions, 2014)
Religious Discourse in Modern Japan explores the introduction of the Western concept of "religion" to Japan in the modern era, and the emergence of discourse on Shinto, philosophy, and Buddhism. Taking Anesaki's founding of religious studies ( shukyogaku ) at Tokyo Imperial University as a pivot, Isomae examines the evolution of this academic discipline in the changing context of social conditions from the Meiji era through the present. Special attention is given to the development of Shinto studies/history of Shinto, and the problems of State Shinto and the emperor system are described in relation to the nature of the concept of religion. Isomae also explains how the discourse of religious studies developed in connection with secular discourses on literature and history, including Marxism.